Evaluation of rockburst risk in deep tunnels considering structural planes based on energy dissipation rate criterion and numerical simulation. (July 2023) - Zhang, Rujiu; Liu, Yaoru; Hou, Shaokang
Highlights: Energy dissipation rate (EDR) criterion was developed for rockburst risk evaluation. EDR contour map can reveal potential damaged zones of rockbursts. Rockbursts in Jinping II drainage tunnel were evaluated and understood using EDR. Joints may increase intensity, delay occurrence and affect locations of rockbursts. Abstract: Risk evaluation of rockbursts is crucial for ensuring the safety and stability of deep-tunnel construction. Structural planes play an important role in the potential for rockbursts to occur, and more related studies are needed. In this paper, a new rockburst criterion based on energy dissipation rate (EDR) index was developed and the role of structural planes in rockburst potential was studied. Firstly, a method of generating structural planes and a viscoplastic constitutive model with internal variables were introduced for numerical simulation using FLAC3D. Then, tunnelling under different hydrostatic pressures was simulated to obtain the values of EDR index and stress-strength/strength-stress ratio indices, and EDR criterion was estimated based on stress-strength/strength-stress ratio criteria. The results show that EDR criterion is: 0∼1 Pa/s (no risk), 1∼3 Pa/s (low risk), 3∼6 Pa/s (medium risk), >6 Pa/s (high risk). Subsequently, the case study of rockbursts in the drainage tunnel of Jinping II hydropower station was conducted considering a nearby fault to validate EDR criterion. The simulation results using EDR are basically consistent with actual rockbursts in terms of the potential location, intensity and time. Finally, the numerical simulations of tunnel excavation considering a joint set with different dip angles were implemented, and the influences of joints on rockbursts were investigated using EDR. Analysis results show that rockbursts are prone to occur on tunnel walls parallel and perpendicular to joints; potential rockburst locations are controlled by local joints and are less affected by geostress distribution. Joints may increase the intensity, delay the occurrence time, and control the pit boundaries of rockbursts. Obtained EDR contours can be used to infer damaged zones of strainbursts and strain-structure slip rockbursts and understand inducing mechanism of rockbursts in Jinping II drainage tunnel. The findings of this study provide insight into the role of structural planes on rockbursts. The presented methodology can be applied to rockburst evaluation and prevention during the construction of deep tunnels.